(untitled) (Palíndromo, 2013)
The prospects of a continued artistic intervention project are presented. Their meaning lays on the creation of an open and collorfull zone at Morro da Mangueira in Rio de Janeiro. In this place modeling, we engender a relational art work trough the proposition of moments for acquaintancy and object production for exchange and interpersonal contact. The research reveals creative and reflective processes involved in environmental awareness, as well as the amplified union of the emotional with the space and the surrounding community. The participants are involved in integrating community / school / university by practicing the approximation between academic knowledge, with its expertise, the teaching knowledge, broad and formal, and the community awareness, rooted in the vital forms of everyday life and preserved in its local memory.